Malaria Microscopy Competency in the Subnational Verification, China: Implications for Malaria Elimination and the Prevention of Malaria Reestablishment. (30th October 2022) - Li, Mei; Huang, Fang; Yin, Jianhai; Yan, He; Zhou, Shuisen; Xia, Zhigui
Abstract : Introduction . Qualified microscopy competency is a key indicator for certification of malaria elimination. To better prepare the country certification and identify the priorities that need improvement to prevent malaria reestablishment, microscopy competency at different levels were assessed in subnational verification of malaria elimination in China. Methodology . Microscopist representatives from centers for disease control and prevention (CDC)/institutes of parasitic diseases (IPD) and medical institutes for malaria diagnosis at the provincial and county levels in the subnational verification were analyzed. Specifically, five provincial microscopist representatives and ten county-level representatives were assessed in each of previously endemic provinces on qualitative identification ( Plasmodium positive or negative) and Plasmodium species identification using standard slides from the National Malaria Diagnosis Reference Laboratory. Results . A total of 100 provincial-level representatives (60 from 42 CDCs/IPDs and 40 from 34 medical institutes) and 200 county-level representatives (61 from 41 CDCs and 139 from 118 medical institutes) were included. The qualitative accuracy was higher than 90% each (P = 0.137 ), but slides with low parasite density were easy to be misdiagnosed as negative. Furthermore, the accuracy of species identification was 80.0% and 83.6% in medical institutes and centers for disease control and prevention (CDCs) at the provincial level (P = 0.407 ) with relatively high misdiagnosis of P. vivax as P. ovale in the latter (16.2%) and 82.0% and 85.0% in medical institutes and CDCs at the county level (P = 0.330 ) for the identification of P. falciparum and non- P. falciparum with higher false-negative in medical institutions (P < 0.001 ). Conclusions . In conclusion, competent microscopy in subnational verification supported the quality in eliminating malaria in China, while the accurate identification of malaria parasites, especially slides with low parasite density still need to be improved through continuous diagnostic platform construction, continuous technological innovation, and targeted training to prevent reestablishment of malaria transmission.